Neka čudna zemlja . A Strange Country - Marinković, Dragan (TRZ Feniks Film Beograd ; RTV Beograd, 1988)
In this poetic art film with surreal scenery and no real time lines, a father, who died far away, asked that his son bury him in his native “Southern land.” He described this land as one of brave and honest people and with a tragic but heroic history. After twenty years of wandering the world, he finally arrives in an archaic country where his father’s language is spoken, but everything else seems absurd and unbelievable and quite different from his father’s story. He can only see greedy politicians with ludicrous laws and scared and inert peasants. Only a few individuals bear any resemblance to his father’s tales, amongst them a crazy pilot who claims he can fly his primitive plane by the strength of his faith. The son finally decides that this cannot be his father’s land and flies off in the pilot’s plane, landing in what is apparently the same country, maybe more modern and a few centuries later.